Amyloid-associated increases in longitudinal report of subjective cognitive complaints - Amariglio, Rebecca E. (Alzheimers Dement (N Y), 2018)
INTRODUCTION: To investigate whether baseline subjective cognitive complaints (SCCs) predict longitudinal decline on neuropsychological testing and whether SCC increases longitudinally, in the setting of high levels of amyloid burden. METHODS: Two hundred seventy-nine clinically normal older participants (mean age = 73.7 ± 6.1 years) from the Harvard Aging Brain Study, a cohort of community-dwelling individuals, were followed longitudinally (4.27 ± 1.35 years) with annual subjective memory questionnaires and neuropsychological assessment. (11)C Pittsburgh compound-B positron emission tomography was used to measure cortical amyloid and to classify status (Aβ+/Aβ−) at baseline. RESULTS: Higher baseline SCC predicted more rapid cognitive decline on neuropsychological measures among those with elevated amyloid (t = −2.18, P < .0001). In addition, longitudinal report of SCC significantly increased over time, with SCC progression most pronounced among Aβ+ individuals (t = 2.24, P = .0005). DISCUSSION: SCC may inform risk for future cognitive decline and track progression of self-perceived decline, particularly in those along the AD trajectory, providing potentially important indicators of clinical meaningfulness in AD prevention trials.